Neighborhood sustainability assessment tools: A systematic review and typology of research - Behrooz Biqaraz; Mahmoud Ghalehnoee; Hassan Mohammadian Mosammam (Sustainable Futures)
Almost two decades after the first neighborhood sustainability assessment tool (NSAT) appeared, research on these tools has grown rapidly and covers diverse perspectives. A critical view of this research helps improve the development and application of NSATs. This systematic review classifies 207 studies by their objectives and identifies key methodological gaps. Using the PRISMA checklist, we selected and analyzed relevant publications in two screening stages. Inductive qualitative content analysis revealed eight main research types. We used a multiple-researcher approach to ensure unbiased classification (Cohen’s kappa = 0.87). For each research type, we highlight specific methodological shortcomings and suggest improvements. Some of these include integrating both qualitative and quantitative methods, adopting methods capable of considering the linkages between indicators when developing a new NSAT, and conducting more longitudinal research when evaluating certified developments or assessing the factors affecting the adoption of the tools. We recommend future studies for evaluating the suitability of known universal NSATs for use in developing countries; developing NSATs for countries with high pollution and emission levels, and so on. The study is grounded in three urban sustainability theories-Transition Theory, Adaptive Governance, and Socio-Technical Regimes-which support the typology and analysis. These frameworks clarify how NSATs contribute to urban sustainability transitions, adaptive practices, and socio-technical change.